2017
DOI: 10.1371/journal.pgen.1006936
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear/cytoplasmic transport defects in BBS6 underlie congenital heart disease through perturbation of a chromatin remodeling protein

Abstract: Mutations in BBS6 cause two clinically distinct syndromes, Bardet-Biedl syndrome (BBS), a syndrome caused by defects in cilia transport and function, as well as McKusick-Kaufman syndrome, a genetic disorder characterized by congenital heart defects. Congenital heart defects are rare in BBS, and McKusick-Kaufman syndrome patients do not develop retinitis pigmentosa. Therefore, the McKusick-Kaufman syndrome allele may highlight cellular functions of BBS6 distinct from the presently understood functions in the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 67 publications
3
26
0
Order By: Relevance
“…(2010) also reported that the BBS disruption causes phenotypes associated with planar cell polarity (PCP) defects in zebrafish; likewise, there are other studies that also showed evidence for similar axial phenotypes by in vivo loss of function methods in zebrafish 21,22 . However, other recent studies 37 do not report early developmental phenotypes typically associated with PCP pathway defects. These possible discrepancies could be attributed to behavior/mutagenic efficiency of the different MOs used.…”
Section: Discussionmentioning
confidence: 90%
“…(2010) also reported that the BBS disruption causes phenotypes associated with planar cell polarity (PCP) defects in zebrafish; likewise, there are other studies that also showed evidence for similar axial phenotypes by in vivo loss of function methods in zebrafish 21,22 . However, other recent studies 37 do not report early developmental phenotypes typically associated with PCP pathway defects. These possible discrepancies could be attributed to behavior/mutagenic efficiency of the different MOs used.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, we have shown that BBS7, which interacts with CCDC28B 10 , enters the nucleus and modulates gene transcription through an interaction with RNF2, a member of the polycomb chromatin remodeling complex 43 . This finding was reinforced recently by a report showing that BBS6 actively translocates between the cytoplasm and nucleus and interacts with the SWI/SNF chromatin remodeling protein SMARCC1 thus affecting gene transcription 44 . In the case of SIN1, the other reported CCDC28B interacting protein linked to cilia length regulation 13 , there are at least five isoforms produced by alternative splicing that present a dynamic sub-cellular localization being found in the plasma membrane, cytoplasm, nucleus, and in the case of the shorter SIN1γ, the basal body 45 47 .…”
Section: Discussionmentioning
confidence: 65%
“…BBS6 (or MKKS) is required for retrograde cellular transport and proper cilia functioning. The zebrafish bbs6 (mkks) morphants have shorter cilia of their Kupffer vesicles [107]. BBS10 and BBS12, localize to the primary cilia of human preadipocytes, where they carry Wnt and Hedgehog receptors [108].…”
Section: Bardet-biedl Syndromementioning
confidence: 99%